2014
DOI: 10.1038/srep06216
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic analysis of NDM-1 Klebsiella pneumoniae in spaceflight reveal mechanisms underlying environmental adaptability

Abstract: The emergence and rapid spread of New Delhi Metallo-beta-lactamase-1 (NDM-1)-producing Klebsiella pneumoniae strains has caused a great concern worldwide. To better understand the mechanisms underlying environmental adaptation of those highly drug-resistant K. pneumoniae strains, we took advantage of the China's Shenzhou 10 spacecraft mission to conduct comparative genomic and transcriptomic analysis of a NDM-1 K. pneumoniae strain (ATCC BAA-2146) being cultivated under different conditions. The samples were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…Population genomic analyses of the bacterial isolates recovered from epidemics have provided unprecedented insights into the evolution of the pathogens, genetic changes in the bacterial genome that contribute to altered virulence, and loci that are under strong selection during natural infection (14)(15)(16)(41)(42)(43)(44)(45)(46). Wholegenome sequencing analyses of ϳ800 strains of GAS serotype M59 from invasive epidemics revealed that the mga locus is under strong selection pressure, suggesting a critical role for the regulatory function of Mga in the pathogenesis of serotype M59 GAS (13,14,17).…”
Section: Discussionmentioning
confidence: 99%
“…Population genomic analyses of the bacterial isolates recovered from epidemics have provided unprecedented insights into the evolution of the pathogens, genetic changes in the bacterial genome that contribute to altered virulence, and loci that are under strong selection during natural infection (14)(15)(16)(41)(42)(43)(44)(45)(46). Wholegenome sequencing analyses of ϳ800 strains of GAS serotype M59 from invasive epidemics revealed that the mga locus is under strong selection pressure, suggesting a critical role for the regulatory function of Mga in the pathogenesis of serotype M59 GAS (13,14,17).…”
Section: Discussionmentioning
confidence: 99%
“…1 It is widely recognized that Kp could cause multiple infections including liver abscess, urinary tract infection and surgical incision infection. Kp is also a potential nosocomial multidrug resistant bacterium.…”
Section: Chinese Medical Sciences Journal June 2017mentioning
confidence: 99%
“…Five genes associated with OmpA were downregulated; these normally play a key role in adhesion. Li et al () reported the same elongated cells in K. pneumoniae after spaceflight. Furthermore, Pyle et al () reported elongated Burkholderia cepacia cells and chains of cells after culture during spaceflight.…”
Section: Discussionmentioning
confidence: 66%
“…A few years later, 15 strains of microorganisms were harbored on the Shenzhou VIII spacecraft, and 2 years later, the Shenzhou X spacecraft, which carried nine different microorganisms, was launched. Phenotypic, genomic, and transcriptomic changes were detected in these microorganisms, including drug resistance mutations and metabolic adaptations to the space environment (Chang et al, ; Guo et al, ; Li et al, ; Su, Chang, & Liu, ; Su et al, ; Zhang, Fang, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%